Stereoselective glycoconjugation of steroids with selenocarbohydrates. Issue 96 (30th September 2016) - Affeldt, Ricardo F.; Santos, Francisco P.; da Silva, Rafael S.; Rodrigues, Oscar E. D.; Wessjohann, Ludger A.; Lüdtke, Diogo S.
Abstract : A methodology that brings together sugar and steroid scaffolds linked by a selenium atom is discussed in this work. Abstract : A methodology that brings together sugar and steroid scaffolds linked by a selenium atom is discussed in this work. A series of 6β and 3α glycoconjugated steroids were achieved by stereoselective nucleophilic substitution of cholesterol, pregnenolone, stigmasterol and sitosterol with different seleno-pyranosides and furanosides.